POLITENESS STRATEGIES IN DIRECTIVE SPEECH ACTS IN TEACHER–STUDENT CLASSROOM INTERACTION IN BORDER AREAS - Viktoria Melati, Felisitas; Sumarni, Margaretha Lidya; Jewarut, Siprianus; Wini, Teresia (Pena Cendekia Insani, 2026)
Teacher–student classroom interaction functions not only to transmit knowledge but also to shape values and learning participation, making directive speech acts and politeness strategies pedagogically significant. This study investigates politeness strategies in directive speech acts within classroom interaction at a border-area elementary school. Using a descriptive qualitative design, data were collected through classroom observation, recordings, field notes, and interviews, and analyzed through speech act theory, Leech’s politeness principle, and a sociopragmatic framework. The findings show that teachers predominantly employ commands and requests, typically mitigated through addressing students by name, explanations, choice-giving, and supportive nonverbal cues, while students’ directives tend to be more direct due to peer familiarity. Politeness strategies are shaped by sociocultural diversity and relational dynamics. These results indicate that directive politeness functions as a pedagogical resource for fostering respectful interaction, student engagement, and culturally responsive communication in border-area classrooms.